2014
DOI: 10.12738/estp.2014.5.1834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cognitive Entry Behaviors and Affective Entry Characteristics on Learning Level

Abstract: In this study, the effect of cognitive entry behaviors and affective entry characteristics on learning level was investigated. The study was conducted on 258 first year students attending the Faculty of Education in the autumn semester of the 2011-2012 academic year. The study was conducted using the relational survey model and data was collected using the "Cognitive Entry Behaviors Test," "Scale of Interest for the Course on Introduction to Education," "Scale of Attitude for the Course on Introduction to Educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…These findings are in conformity with a study by Caliskan (2014) which investigated the effects of entry behavior on learning at higher level in Meram, Turkey. The study found out that good entry behavior raises the learning level at primary and secondary education, while poor entry behavior lowers it.…”
Section: Analysis Of Responses By Chairpersons Of Parents Association...supporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in conformity with a study by Caliskan (2014) which investigated the effects of entry behavior on learning at higher level in Meram, Turkey. The study found out that good entry behavior raises the learning level at primary and secondary education, while poor entry behavior lowers it.…”
Section: Analysis Of Responses By Chairpersons Of Parents Association...supporting
confidence: 92%
“…Caliskan (2014) defines students' entry behavior as a form of prelearning required to study a specific unit or course. A study by Caliskan (2014) investigated the effects of entry behavior on learning at higher level in Meram, Turkey. The study found out that pre-learning is a key variable regarding level of learning at higher level and that good entry behavior raised the learning level at primary and secondary education, while poor entry behavior lowered it.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…They serve as standards for evaluating an applicant's potential for learning at a certain level of education or training (NACTE, 2019;European Parliament, 2014). According to studies, this prerequisite may include both cognitive and non-cognitive qualities, such as the learner's prior knowledge and personality traits; however, cognitive qualities were found to be crucial for student achievement, which is determined through academic grades (Brunello & Schlotter, 2011;Çalişkan, 2014;Kaya & Akdemir, 2016;Nakayama et al, 2021;Ndege, et al, 2018). However, this recognition does not downplay the significance of the learning process itself in transferring desired knowledge, abilities, and attitudes (World Bank, 2014).…”
mentioning
confidence: 99%